Writing Skill Learning Strategies among Non- Native Arabic Speakers in Jordan - Mohammed Ali Alkhawaldeh; Thaer Bassam Barasneh (Deanship of Scientific Research (DSR), the University of Jordan, 2023)
Objectives: The study sought to determine the most popular writing learning techniques among non-native Arabic speakers in Jordan and whether differences in their use according to factors like gender and academic standing were statistically significant. Methods: The researcher created a scale of thirty items, divided into cognitive, metacognitive, and socio-affective methods, to accomplish the study's objectives. The measure was used with (120) Chinese undergraduate students at Jordanian and Yarmouk universities studying Arabic language and literature. Results: According to the study's findings, socio/affective techniques were adopted by high-level pupils more frequently than cognitive and meta-cognitive ones. The findings also indicated that there was a statistically significant difference due to the gender variable on students' rates of socio-affective strategies in learning writing skills, favoring females, and that there was a statistically significant difference due to the study level on their rates of cognitive and meta-cognitive strategies, favoring third-year students and above, but less favoring second-year students in socio-affective strategies. Conclusions: Several recommendations were made in light of the study's findings, including urging non-Arabic speakers to adopt writing skill acquisition techniques, particularly cognitive and metacognitive ones.